2012 First International Conference on Agro- Geoinformatics (Agro-Geoinformatics) 2012
DOI: 10.1109/agro-geoinformatics.2012.6311656
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of soil moisture from multi-polarized SAR data over wheat coverage areas

Abstract: Radar data has important implications in agricultural fields monitoring, particularly in the retrieval of the crop height, leaf area index (LAI) and soil moisture information. The objective of this study was to estimate soil moisture contents based on multi-polarized synthetic aperture radar (SAR) data acquired over wheat fields. The soil moisture inversion algorithm was based on semi-empirical backscattering models and the prior estimation of wheat heights ( h ) and wheat water contents ( WC ) from SAR data(R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The study site was a 450 hectare farmland composed of irrigated and non-irrigated grassland for hay in : IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, n° 99, 2015. p. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] production. Located in southeastern France (center: 43.64°N, 5.01°E, Figure 1), this relatively flat site is characterized by a Mediterranean climate, with a rainy season between September and November and an average cumulative rainfall between 350 mm and 800 mm [23].…”
Section: A Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The study site was a 450 hectare farmland composed of irrigated and non-irrigated grassland for hay in : IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, n° 99, 2015. p. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] production. Located in southeastern France (center: 43.64°N, 5.01°E, Figure 1), this relatively flat site is characterized by a Mediterranean climate, with a rainy season between September and November and an average cumulative rainfall between 350 mm and 800 mm [23].…”
Section: A Study Areamentioning
confidence: 99%
“…Recently, Betbeder et al [45] showed that the Shannon entropy is highly correlated with the fragmentation of hedgerows. The Pauli decomposition components corresponding to the three diagonal in : IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, n° 99, 2015. p. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] elements of the coherency matrix ( [46]), each have a specific scattering mechanism: (HH+VV) represents the surface scattering, (HV+VH) is associated with volume scattering, and (HH-VV) indicates doublebounce scattering. Surface scattering dominates when the radar signal is primarily reflected from the canopy top.…”
mentioning
confidence: 99%
“…These results encourage the use of X-band with medium angle (about 30°) in both HH and HV polarizations for soil moisture estimates over grassland. For C and X-bands SAR data, studies showed that it is possible to estimate the soil moisture with accuracy from 2 to 8 Vol.% (RMSE "Root Mean Square Error") (Gherboudj et al, 2011;He et al, 2014;Notarnicola et al, 2006;Prévot et al, 1993;Sikdar and Cumming, 2004;Wang et al, 2011;Yang et al, 2012;Yu and Zhao, 2011;Zribi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The WCM is the most commonly used model to estimate soil moisture in the presence of vegetation cover because it uses a simple formulation and consequently, it could be easily inverted [21,29,[31][32][33][45][46][47][48]. In the WCM, the total backscattered signal is equal to the sum of vegetation contribution and soil contribution attenuated by the vegetation layer.…”
Section: Radar Backscattering Modelmentioning
confidence: 99%